Tooth loss trajectories and their association with all-cause mortality among older Chinese adults - Zhang, Xiaoming; Zeng, Rui; Ye, Dongmei; Shi, Mengxia; Zhu, Aizhang; Chen, Lihuan; Fan, Tenghui; Zhu, Ke; Xie, Fayi; Zhu, Wan; Zeng, Yufei; Wang, Jiang; et al. (Frontiers in Oral Health, 2025)
BackgroundThe association between tooth loss trajectories and all-cause mortality has not been sufficiently explored. This study aims to examine the relationship between tooth loss trajectories and all-cause mortality in Chinese adults aged 65 years and older.MethodsThis study included 3,726 participants from the Chinese Longitudinal Healthy Longevity Study (CLHLS). The inclusion criteria required participants to be aged 65 years or older, with complete data on tooth count at baseline and at least one follow-up survey. Participants were excluded if they had missing data on death, time to death, or if their they reported tooth count showed an abnormally high increase. The mean age of participants was 85.16 ± 10.7 years. To identify distinct trajectories of tooth loss, growth mixture models (GMM) were employed. Cox regression analysis was utilized to assess the association between tooth loss trajectories and all-cause mortality. Sensitivity analyses were conducted to test the robustness of the findings, while subgroup analyses were performed to explored potential variations in association across different demographic groups.ResultsThe prevalence of edentulism at baseline was 37.13%, with a cumulative incidence of 15.8% over 10-year period. Three distinct tooth loss trajectories were identified during follow-up of 9.41 years: (1) progressively mild loss: comprising 312 participants (8.37%); (2) progressively severe loss, comprising 505 participants (13.55%); and (3) edentulism group, comprising 2,909 participants (78.07%). The median follow-up times for each group were 5.91 years, 3.44 years, and 1.84 years, respectively. During the follow-up period, the number of deaths were 114 (36.54%) in the progressively mild loss group, 274 (54.26%) in the progressively severe loss group, and 2,284 (78.51%) in the edentulism group. Compared to the progressively mild loss group, the hazard ratio (HR) for all-cause mortality was 1.29 (95% CI, 1.01–1.64) in the progressively severe loss group, and 1.60 (95% CI, 1.28–1.99) in the edentulism group.ConclusionsThis study identified three distinct tooth loss trajectories among older Chinese adults, with the edentulism group exhibiting the strongest association with all-cause mortality. These findings highlight the crucial importance of maintaining oral health and preserving natural teeth to promote longevity and improve overall health outcomes in older adults.